An Organic Cathode Material S‐3Q@MWCNT with Monoelectrochemical Conversion Phase for Highly Reversible Lithium Batteries. Issue 12 (29th October 2021) - He, Zhipeng; Zhang, Jingjing; Guo, Xiumei; Kang, Hai; Wang, Zhihua; Liu, Yilin; Wang, Minghua; Zhang, Hanping
Abstract : A facile strategy to synthesize organic cathode material using triquinoxaline (3Q) and elemental sulfur (S) is reported. The 3Q material is a kind of multiredox phase‐transiting composite with a theoretical specific capacity of 418 mA h g −1 and a poor cycling performance. By adding S to 3Q@multiwalled carbon nanotubes (MWCNTs) at 165 °C with a mass ratio of 1:4, S and 3Q are chemically matched to form an organic composite S‐3Q@MWCNT. Interestingly, it is found that the as‐prepared sample exhibits a single‐electrochemical phase transition with a higher specific capacity of 608 mA h g −1 at 0.1C rate. The mass ratio of 1:4 indicates that the capacity of S is equal to the capacity of 3Q, and the monoredox conversion phase suggests that S and 3Q are electrochemically matched. These results show that the chemical matching point is consistent with the electrochemical matching point. The as‐prepared S‐3Q@MWCNT composite presents a good cycling performance. In the absence of any additives, especially without the assistance of coated separators, the coulombic efficiency is stable at around 100% for 400 cycles. It is believed that the monophase redox process of the as‐prepared S‐3Q@MWCNT improves the cycling performance. Abstract : When the mass ratio of sulfur to 3Q is 1:4, the redox peak changes from two pairs of 3Q and S to one pair of S‐3Q@MWCNT, making the active material exhibit single‐phase electrochemical reaction. This procedure does not involve complex phase transitions. The structure is thereby stable during charging and discharging, which is beneficial for better performance.